2021
DOI: 10.1038/s41598-021-94284-4
|View full text |Cite
|
Sign up to set email alerts
|

Using corneal confocal microscopy to compare Mecobalamin intramuscular injections vs oral tablets in treating diabetic peripheral neuropathy: a RCT

Abstract: This randomized controlled study used corneal confocal microscopy (CCM) to compare the efficacy of Mecobalamin intramuscular injections vs oral tablets in treating mild to moderate diabetic peripheral neuropathy (DPN) by detecting early nerve fiber repair. Enrolled patients were randomized approximately 1:1 to receive Mecobalamin intramuscular injections (0.5 mg/day, 3 times/week) or Mecobalamin oral tablets (1.5 mg/day) for 8 weeks. Primary outcome was change of inferior whorl length (IWL) from baseline. Seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…erefore, mecobalamin was found to be effective in treating disease or treatment-induced peripheral neuropathy [9][10][11], which is consistent with the results of the present study. Troxerutin, also known as vitamin P4, has been shown to inhibit red blood cell and platelet aggregation, inhibit apoptosis, protect nerves, improve microcirculation, increase blood oxygen content, and promote angiogenesis [12,27].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…erefore, mecobalamin was found to be effective in treating disease or treatment-induced peripheral neuropathy [9][10][11], which is consistent with the results of the present study. Troxerutin, also known as vitamin P4, has been shown to inhibit red blood cell and platelet aggregation, inhibit apoptosis, protect nerves, improve microcirculation, increase blood oxygen content, and promote angiogenesis [12,27].…”
Section: Discussionsupporting
confidence: 91%
“…[ 9 ]. Previous studies have found that mecobalamin tablets were effective in treating disease or treatment-induced peripheral neuropathy, including diabetic peripheral neuropathy and FOLFOX4 chemotherapy-induced peripheral neuropathy (CIPN) [ 10 , 11 ]. Troxerutin, also known as vitamin P4, is a derivative of the naturally occurring bioflavonoid rutin, found in tea, coffee, grains, and many vegetables and fruits [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been pointed out that mecobalamin is an endogenous B 12 , which can participate in the carbon unit cycle and has an important role in the homocysteine synthesis protein acid transmethylation reaction, and is extremely suitable for lower limb neuropathy [10]. Meanwhile, methylcobalamin has strong affinity for nerves, which can promote nerve regeneration and increase the blood flow in the nerve endothelium, regulate the neurotrophic state, and enhance the conduction speed of motor nerves [11]. Infrared therapy instrument is an important physical therapy for diabetic foot, which can irradiate deep tissues by 3 Disease Markers combining infrared and red light, and the heat generated during infrared therapy can stimulate local blood vessels by acting on damaged parts, which can effectively dilate, improve local blood circulation, reduce nerve tissue hypoxia and ischemia, and restore local tissue oxygen and nutrient supply, thus shortening the healing time of the wound [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Just recently, CCM has been applied in two randomized clinical trials: One confirmed CCM sensitive enough to detect the superior efficacy of 8-week mecobalamin intramuscular injection treatment for DPN compared with the oral tablet treatment [ 119 ]. The other, the BOND study, which is still ongoing, aims to assess the effects of treatment with benfotiamine, compared with placebo, in participants with T2DM and mild-to-moderate symptomatic DPN, with the primary endpoint being a change in CNFL after 12 months of treatment and secondary endpoints including other CCM measures [ 120 ].…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…ImageJ, particularly with its plugin NeuronJ, currently represents one of the most frequently used methods to conduct a semi-automated analysis of the sub-basal nerve plexus, since it has been used in multiple studies to assess parameters such as IWL, CNFL, CNFD, CNBD, beading frequencies, and corneal nerve thickness [ 30 , 42 , 48 , 84 , 88 , 90 , 93 , 119 ]. It is a validated open-source image analysis platform developed by the National Institutes of Health (NIH; Bethesda, MD, USA), which includes NeuronJ, a semi-automated nerve-tracing plugin that intuitively draws a line over the center of a visible nerve fiber as the nerve is traced [ 121 , 122 , 123 ].…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%